2023
DOI: 10.3390/nu15030734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Circadian Rhythm Disturbance on the Human Musculoskeletal System and the Importance of Nutritional Strategies

Abstract: The circadian system in the human body responds to daily environmental changes to optimise behaviour according to the biological clock and also influences various physiological processes. The suprachiasmatic nuclei are located in the anterior hypothalamus of the brain, and they synchronise to the 24 h light/dark cycle. Human physiological functions are highly dependent on the regulation of the internal circadian clock. Skeletal muscles comprise the largest collection of peripheral clocks in the human body. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 131 publications
0
12
0
Order By: Relevance
“…Women have been found to be more vulnerable to the symptoms of depression (15)(16)(17) and anxiety (16, 18) during the COVID-19 pandemic. Nurses had a greater likelihood of developing depression than others, but any job type of healthcare worker developed anxiety at equal odds (6). And studies also revealed that healthcare workers with bachelor's degrees had significantly higher depression and anxiety than those with different education levels (19,20).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Women have been found to be more vulnerable to the symptoms of depression (15)(16)(17) and anxiety (16, 18) during the COVID-19 pandemic. Nurses had a greater likelihood of developing depression than others, but any job type of healthcare worker developed anxiety at equal odds (6). And studies also revealed that healthcare workers with bachelor's degrees had significantly higher depression and anxiety than those with different education levels (19,20).…”
Section: Introductionmentioning
confidence: 98%
“…Facing the unprecedented situation, healthcare workers have made great efforts to provide medical treatment and care to control the epidemic quickly during the COVID-19 pandemic and faced excessive workloads and psychological pressure, thereby having a large proportion of psychological problems. Compared to other occupational groups, they were particularly vulnerable to psychological problems (5)(6)(7)) and more than one-third of healthcare workers experienced anxiety and depression during the COVID-19 pandemic globally (8) and in China (9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting with the circadian cycle [ 7 ], melatonin is involved in a series of biochemical processes related to: reducing oxidative stress [ 8 ], increasing aerobic performances [ 9 ], tissue repair [ 10 ], muscle adaptation and skeletal muscle capacity [ 11 ], sleep and neuroprotection [ 12 ], blood pressure [ 13 ], metabolic diseases [ 14 ], cancer [ 15 ], rheumatic diseases [ 16 ], trauma and accidents [ 17 ], stimulation of cartilage matrix development [ 18 ], cardiovascular diseases [ 19 ], arthritis [ 20 ], and depression [ 21 ]. In order to have an overview of all of melatonin’s connections with the body’s health level, one can imagine a spiral scheme of its effects on some diseases or conditions of the body ( Figure S1 , see supplementary material ).…”
Section: Introductionmentioning
confidence: 99%